Colonialism and race in Luso-Hispanic literature - Branche, Jerome; ebrary, Inc. (Columbia [Missouri] : University of Missouri Press, 2006)
"Branche examines a wide variety of Latin American literature and discourse to show the extent and range of racist sentiments throughout the culture. He argues that racism in the modern period (1415-1948) was a tool used to advance Spanish and Portuguese expansion, colonial enterprise, and the international development of capitalism"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Blacks in literature; Latin American literature -- History and criticism; Race in literature; Racism in literature; Slavery in literature; Electronic books